A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease. - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
BACKGROUND: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. OBJECTIVE: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. METHODS: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. RESULTS: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. CONCLUSION: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
EVALuna2:470167

A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
Background: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. Objective: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. Methods: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. Results: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. Conclusion: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
CRIS-Team Scopus Importer:2021-10-29
Keywords: affective pictures; anhedonia; apathy; depression; hyposmia; non-motor symptoms; Parkinson's disease; Sniffin' Sticks

CSF1R-Mediated Myeloid Cell Depletion Prolongs Lifespan But Aggravates Distinct Motor Symptoms in a Model of Multiple System Atrophy - Battis, Kristina; Florio, Jazmin B.; Mante, Michael; Lana, Addison; Naumann, Isabel; Gauer, Carina; Lambrecht, Vera; Müller, Sarina Katrin; Cobo, Isidoro; Fixsen, Bethany; Kim, Ha Yeon; Masliah, Eliezer; et al. (Journal of Neuroscience, 2022)
As the CNS-resident macrophages and member of the myeloid lineage, microglia fulfill manifold functions important for brain development and homeostasis. In the context of neurodegenerative diseases, they have been implicated in degenerative and regenerative processes. The discovery of distinct activation patterns, including increased phagocytosis, indicated a damaging role of myeloid cells in multiple system atrophy (MSA), a devastating, rapidly progressing atypical parkinsonian disorder. Here, we analyzed the gene expression profile of microglia in a mouse model of MSA (MBP29-ha-syn) and identified a disease-associated expression profile and upregulation of the colony-stimulating factor 1 (Csf1). Thus, we hypothesized that CSF1 receptor-mediated depletion of myeloid cells using PLX5622 modifies the disease progression and neuropathological phenotype in this mouse model. Intriguingly, sex-balanced analysis of myeloid cell depletion in MBP29-ha-syn mice revealed a two-faced outcome comprising an improved survival rate accompanied by a delayed onset of neurological symptoms in contrast to severely impaired motor functions. Furthermore, PLX5622 reversed gene expression profiles related to myeloid cell activation but reduced gene expression associated with transsynaptic signaling and signal release. While transcriptional changes were accompanied by a reduction of dopaminergic neurons in the SNpc, striatal neuritic density was increased upon myeloid cell depletion in MBP29-ha-syn mice. Together, our findings provide insight into the complex, two-faced role of myeloid cells in the context of MSA emphasizing the importance to carefully balance the beneficial and adverse effects of CSF1R inhibition in different models of neurodegenerative disorders before its clinical translation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: colony-stimulating factor 1 receptor; motor function; multiple system atrophy; myeloid cells; neuron-micro-glia interaction; PLX5622

Parkinson's disease or multiple system atrophy: potential separation by quantitative susceptibility mapping - Marxreiter, Franz; Lambrecht, Vera; Mennecke, Angelika; Hanspach, Jannis; Jukic, Jelena; Regensburger, Martin; Herrler, Jürgen; German, Alexander; Kassubek, Jan; Groen, Georg; Mueller, Hans-Peter; Laun, Frederik Bernd; et al. (Therapeutic Advances in Neurological Disorders, 2023)
Background:Due to the absence of robust biomarkers, and the low sensitivity and specificity of routine imaging techniques, the differential diagnosis between Parkinson's disease (PD) and multiple system atrophy (MSA) is challenging. High-field magnetic resonance imaging (MRI) opened up new possibilities regarding the analysis of pathological alterations associated with neurodegenerative processes. Recently, we have shown that quantitative susceptibility mapping (QSM) enables visualization and quantification of two major histopathologic hallmarks observed in MSA: reduced myelin density and iron accumulation in the basal ganglia of a transgenic murine model of MSA. It is therefore emerging as a promising imaging modality on the differential diagnosis of Parkinsonian syndromes. Objectives:To assess QSM on high-field MRI for the differential diagnosis of PD and MSA. Methods:We assessed 23 patients (nine PDs and 14 MSAs) and nine controls using QSM on 3T and 7T MRI scanners at two academic centers. Results:We observed increased susceptibility in MSA at 3T in prototypical subcortical and brainstem regions. Susceptibility measures of putamen, pallidum, and substantia nigra reached excellent diagnostic accuracy to separate both synucleinopathies. Increase toward 100% sensitivity and specificity was achieved using 7T MRI in a subset of patients. Magnetic susceptibility correlated with age in all groups, but not with disease duration in MSA. Sensitivity and specificity were particularly high for possible MSA, and reached 100% in the putamen. Conclusion:Putaminal susceptibility measures, in particular on ultra-high-field MRI, may distinguish MSA patients from both, PD and controls, allowing an early and sensitive diagnosis of MSA.
CRIS-Team WoS Importer:2023-03-17